PENDIDIKAN PEREMPUAN DI MATA KIAI HAJI AHMAD DAHLAN - Rohmad Qomari (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Education for women—with regular fashion—on Kiai Haji Ahmad Dahlan’s era practically didn’t exist, or only given little attention. Women at that time did not allowed outside home, even stay in her room or kitchen. This condition motivates Kiai Haji Ahmad Dahlan to change gradually. From the foundation of Muhammadiyah, Ahmad Dahlan have serve his house and time to women teaching, where he himself teaching or sometimes substituted by his wife, that also have fluent in Islamic knowledge. Kiai Haji Ahmad Dahlan believed that the world would not make complete progress when women only left behind, in the kitchen. He gather women and then give them teaching and course, that specific for mothers. On 1914, this course became organization entitled Sapatresna (who loving).